Eksistensi Perempuan dalam Mempertahankan Kesenian Talempong Gandang Lasuang di Sikapak Timur, Kota Pariaman - Yola Sumeta Rahyu; Susandra Jaya; I Dewa Nyoman Supenida; Syahri Anton (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Talempong Gandang Lasuang is dedicated to the diverse traditional Minangkabau culture, whose culture and identity are widespread. In general, many actors are prominent in the field of social change, yet amidst modernization and social change. This research combines qualitative methods with a descriptive framework. Data based on extensive observation, observation, and documentation demonstrate the long-known importance of Talempong Gandang Lasuang. The research results show that women's presence is evident through their active involvement as performers, cultural inheritors, trainers, and promoters of artistic activities. Experiences of participating in the regeneration process include attending Talempong Gandang Lasuang's post-regeneration training and participating in the regeneration process. Despite the decline in interest from the younger generation and the influence of popular culture, women continue to demonstrate a strong commitment to preserving this art form. Therefore, Talempong Gandang Lasuang should be considered a high pillar in the province of Sikapak Timur, Pariaman City.